Managing Liquidity - Zeng, Zhixiong; Jin, Yi (Management Science, 2023)
This paper studies how liquidity management affects asset markets and aggregate economic performance. We explore the connection between liquidity allocation and capital allocation. The policy that changes the liquidity premia on assets has broad implications for private-sector behavior and market efficiency. Liquidity tightening, that is, a reduction in the aggregate quantity of liquid debt, is associated with credit loosening, that is, an increase in funds raised through the issuance of private liquid debt. A positive liquidity premium on debt is required for capital-allocation efficiency, while a zero-liquidity premium is required for liquidity-allocation efficiency. The optimal policy balances these two considerations. Government purchase of private debt is needed to support low interest rates. The analysis is extended to incorporate the liquidity differential between public and private debt and partially liquid capital. This paper was accepted by Lukas Schmid, finance. Funding: This work was supported by the National Natural Science Foundation of China [Grant 71973058]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2022.4559 .